The Problematic of Bankruptcy Offenses in Affirming the Parameters Between Business Failure and Fraudulent Bankruptcy in Indonesia - Lalu Bayu; Dwi Kusumo Wardhani (Indonesian Journal Publisher, 2026)
Bankruptcy criminal offenses are legal instruments that function to maintain trust in economic activities and to protect the interests of creditors from fraudulent acts by debtors. In the Indonesian legal system, regulations concerning bankruptcy are related to Law Number 37 of 2004 on Bankruptcy and Suspension of Debt Payment Obligations, which is oriented towards civil and procedural aspects, as well as the National Criminal Code through Law Number 1 of 2023, which links criminal liability to bankruptcy conditions, including for business actors and corporations. Nevertheless, these regulations still give rise to fundamental problems in the form of a normative gap regarding the absence of clear parameters to distinguish between legitimate business failure and bankruptcy involving elements of fraud. This normative gap has implications for legal uncertainty in determining the limits of criminal liability, and it has the potential to lead to the criminalization of entrepreneurs acting in good faith or to suboptimal law enforcement against fraudulent acts in bankruptcy. This research aims to (1) analyzing the normative gaps in the regulation of criminal bankruptcy offenses related to the distinguishing parameters between business risk and criminal acts, as well as (2) Studying the concept of reforming bankruptcy criminal offenses in a fair manner within the Indonesian legal system. The research method used is normative juridical with a statutory approach and a conceptual approach. Therefore, it is necessary to add and reinforce regulations regarding indicators of bad faith as well as distinguishing parameters between business failure and fraudulent bankruptcy, accompanied by the development of an adaptive and proportional law enforcement mechanism, in order to realize legal certainty and justice within the bankruptcy legal system.